(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2020)
Objective: To investigate how botulinum toxin type A (BTXA) contributes to the development of hypertrophic scars. Methods: Isolated and cultivated HSF cells came from hypertrophic scars. The expressions of TGF-β1, FN, and Col1 in normal and hypertrophic scar tissues were determined using immunohistochemistry (IHC) assays. In HSF cells, the expressions of α-SMA, Col1, and FN1 were assessed using immunoblot techniques, along with the expressions and phosphorylation of p38, ERK, and JNK. To determine how BTXA affected the proliferation and migration of HSF cells, researchers used the CCK-8 and Transwell assays. Findings: The MAPK pathway was inhibited in hypertrophic scar fibroblasts by BTXA (p < 0.01). Additionally, it inhibited the development and motility of HSF via the MAPK pathway (p < 0.01) and reduced the amount of collagen deposits in hypertrophic scars (p < 0.01). The results show that BTXA inhibits hypertrophic scarring via the MAPK pathway, suggesting that it may be useful as a medication to treat this condition. Topics covered include hypertrophic scar, fibroblasts, collagen deposition, Botulinum toxin type A (BTXA), and the MAPK pathway.